Equivalent Circuits for Microwave Metamaterial Planar Components - Romolo Marcelli (Sensors, 2024)
Metamaterial components and antennas are based on the general understanding that an artificial structure composed of adequately designed and manufactured elementary cells or arrays has unusual resonance and propagation properties. Metamaterials exhibit equivalent values of the dielectric constant and magnetic permeability that are both negative simultaneously, in contrast with ordinary materials. Single elements, periodic, or quasi-periodic configurations can be suitable for a metamaterial response. In this paper, equivalent circuits for microwave propagation and resonance are compared, deriving a lumped element modeling complementary to those already available in the literature, with a particular focus on planar resonating devices and calculating the effective value for the dielectric constant and the magnetic permeability directly from experimental findings using the impedance (Z-parameters) notation.